The Effectiveness of Mind Mapping For Writing Procedure Text By Using Instagram - Farih, Abdullah; Sakinah, Mawadah (Kayon Media, 2023)
The students should master four basic skills in English, such as listening, reading, speaking and writing. Writing is one of students’ basic skills to master especially in writing procedure. There are some technique and media to teach in the class. One of the techniques is mind mapping and the media is Instagram. The students learn about procedure text by using mind mapping and Instagram, it could give motivation to improve their writing. This research used quasi-experimental design. It was conducted in SMKN 1 Lamongan. The population of this research is tenth grade. The samples were tenth AKL 1 and tenth AKL 2 the total samples were 68 students with non-equivalent control group design. It can be concluded that there is significant effect of mind mapping for writing procedure text by using Instagram of Tenth AKL SMKN 1 Lamongan in academic year 2022/2023.